Where artisanal mines and forest meet: socio-economic and environmental impacts in the Congo Basin - Ingram, V.J.; Tieguhong, J.C.; Schure, J.; Nkamgnia, E.M.; Tadjuidje, M. H. (2011)
While mineral exploitation can provide significant income and employment, it may negatively impact the environment, being ultimately detrimental to livelihoods in the long term. The consequences of mining are of concern in high value forest ecosystems such as the Sangha Tri-National (TNS) landscape covering Cameroon, the Central African Republic and Republic of the Congo. This paper captures the socio-economic and environmental impacts of small-scale mining in the TNS. Using structured questionnaires, consultations and observation, diamonds and gold were found to contribute directly to the livelihoods of at least 5% of the landscape’s population. Although up to eight income-generating strategies are used, mining contributes on average to 65% of total income and is used mainly to meet basic needs. A gold miner’s average income is US$ 3.10 a day, and a diamond miner earns US$ 3.08, making them slightly wealthier than an average Cameroonian and three times wealthier than an average non-miner in the TNS. Environmental impacts were temporary, low impact and of limited scale. However, with mining likely to increase in the near future, an increasing population and miners’ low environmental awareness, measures are needed to ensure and reinforce the positive impact of artisanal mining on livelihoods and maintain its low environmental footprint in the TNS landscape